2017
DOI: 10.1111/dom.12946
|View full text |Cite
|
Sign up to set email alerts
|

Evidence connecting old, new and neglected glucose‐lowering drugs to bile acid‐induced GLP‐1 secretion: A review

Abstract: Bile acids are amphipathic water-soluble steroid-based molecules best known for their important lipid-solubilizing role in the assimilation of fat. Recently, bile acids have emerged as metabolic integrators with glucose-lowering potential. Among a variety of gluco-metabolic effects, bile acids have been demonstrated to modulate the secretion of the gut-derived incretin hormone glucagon-like peptide-1 (GLP-1), possibly via the transmembrane receptor Takeda G-protein-coupled receptor 5 and the nuclear farnesoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 74 publications
0
10
1
Order By: Relevance
“…Since metformin is the consensus first‐line medical treatment for type 2 diabetes, recognizing how its presence impacts the effectiveness of next‐line agents such as DPP‐4 inhibitors could inform clinical practice and guideline development. Because there exists a potential GLP‐1‐based mechanism by which metformin could enhance the effect of DPP‐4 inhibitors, DPP‐4 inhibitors provide a sensible opportunity to study interactions with metformin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since metformin is the consensus first‐line medical treatment for type 2 diabetes, recognizing how its presence impacts the effectiveness of next‐line agents such as DPP‐4 inhibitors could inform clinical practice and guideline development. Because there exists a potential GLP‐1‐based mechanism by which metformin could enhance the effect of DPP‐4 inhibitors, DPP‐4 inhibitors provide a sensible opportunity to study interactions with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, how different medication classes interact to determine CV outcomes in type 2 diabetes is poorly understood. Since metformin is the consensus first-line medical treatment for type 2 diabetes, 1 exists a potential GLP-1-based mechanism by which metformin could enhance the effect of DPP-4 inhibitors, 8,9 DPP-4 inhibitors provide a sensible opportunity to study interactions with metformin.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Bile acid sequestrants regulate glucose homeostasis, at least in part by modulating FXR- and TGR5-mediated pathways. 66,67 …”
Section: Is Modulating Bile Acid Signaling a Potential Pharmacologmentioning
confidence: 99%
“…Recently, a meta-analysis of the three major DPP-4 inhibitor cardiovascular outcomes trials (CVOTs) suggested that baseline metformin use may have a moderating effect on cardiovascular outcomes in DPP-4 inhibitor use. 10 DPP-4 inhibitors prevent the degradation of active glucagon-like peptide-1 (GLP-1), 8 and metformin 11,12 or α-glucosidase inhibitors 13,14 increase circulating GLP-1 levels in clinical studies. Therefore, it is plausible that these drugs could interact synergistically.…”
Section: Introductionmentioning
confidence: 99%